(untitled) (Revista de Artes Marciales Asiáticas, 2013)
Background: It is theorized that the development of the ability to stabilize the trunk may improve the performance of a judoka because it improves body balance control and optimizes force transmission from the lower extremities to the upper limbs. However, there is a lack of scientific evidence to establish a clear relationship between trunk stability and performance in judo. Aim: The purpose of this study was to determine whether the quantification of trunk stability and muscular strength and endurance allowed differentiation between national level (n = 7) and international level judoka (n = 6). In addition, the relationship between trunk stability and muscular strength and endurance of the muscles involved in trunk stability control was analyzed. Method: To assess trunk stability, trunk responses to sudden loads applied by a pneumatic mechanism were analyzed, as well as trunk postural control through an unstable sitting paradigm. Muscular strength and endurance were assessed via a flexion and extension trunk test using an isokinetic dynamometer. Results/Conclusions: International level judokas showed lower CoP displacement in the most complex task in unstable seat (7.00 ± 1.19 vs 8.93 ± 1.45 mm, T = .025) and higher absolute and relative peak torque in extensor muscles (7.05 ± 0.87 vs 5.74 ± 0.72 Nm, T = .013) than national level judoka. According to these results, core stability and trunk muscular condition are important qualities in the physical training of elite judoka. Correlational analysis found no relation between the analyzed variables, thus muscular strength and endurance appear to have a non-significant effect on performance in the trunk stability tests.